Should We Make More Bone or Not, As Told by Kisspeptin Neurons in the Arcuate Nucleus - Herber, Candice B.; Ingraham, Holly A. (Seminars in Reproductive Medicine, 2019)
Since its initial discovery in 2002, the neuropeptide Kisspeptin (Kiss1) has been anointed as the master regulator controlling the onset of puberty in males and females. Over the last several years, multiple groups found that Kiss1 signaling is mediated by the 7TM surface receptor GPCR54. Kiss1 mRNA is highly enriched in the basal medial and lateral subregions of the arcuate nucleus (ARC) in the medial basal hypothalamus. Thus, Kiss1ARC neurons reside in a unique anatomical location ideal for sensing and responding to circulating steroid hormones as well as nutrients. Kiss1 expression is highly responsive to fluctuations of the gonadal hormone, estrogen, with nearly 90% of Kiss1ARC neurons expressing the nuclear hormone estrogen receptor alpha (ERa). Here we review recent research that extends the function of Kiss1ARC neurons beyond the regulation of puberty and highlight their emerging, novel roles in controlling energy allocation, behavioral outputs, and sex-dependent bone remodeling in females. Indeed, some of these previously unknown functions for Kiss1 neurons are quite striking as exemplified by the remarkable increase in bone mass after manipulating estrogen signaling in Kiss1ARC neurons. Taken together, we suggest that Kiss1ARC neurons are highly sensitive to nutritional and hormonal cues that dictate energy utilization and reproduction.
Keywords: kisspeptin; estrogen; arcuate nucleus; bone